Banana cream pie murder [large type] - Fluke, Joanne, 1943- (Fluke, Joanne, 1943- Hannah Swensen mystery., 2017)
A romantic seven-day cruise is the perfect start to bakery owner Hannah Swensen's marriage. However, with a murder mystery heating up in Lake Eden, Minnesota, it seems the newlywed's homecoming won't be as sweet as she anticipated.